TERAPI MUSIK DAN TINGKAT KECEMASAN PASIEN PREOPERASI - Savitri, Wenny; Fidayanti, Nani; Subiyanto, Paulus (MEDIA ILMU KESEHATAN, 2016)
Background: Surgery is one of medical interventions which can cause fear, anxiety, and stressed because of its effects toward the integrity of body and soul. Nurses have significant roles in any preoperative care which is helping patients to decrease preoperative anxiety by using complementary therapy. The use of music therapy as one of the complementary therapies is not common in Indonesia. Therefore, scientific studies to prove the role of this therapy to decrease the level of anxiety of pre-operative patients is needed. Objective: To investigate the effects of music therapy in reducing anxiety levels of preoperative patients. Methods: A quasy experimental study with pre-test and post-test design with control group was applied to 50 respondents from medical ward in Panembahan Senopati Hospital of Yogyakarta who met the inclusion criteria.Dara were then analyzed by using t-test statistical analysis. Results: The control group showed the increased value of anxiety level of0.8 without music intervention (t= -1503, df = 24, p<.05), whereas the intervention group showed the decreased value of anxiety level of -5.52 (t=5.081, df=24, p<.05). Meanwhile the independent t-test results for both groups showed a significant difference between group (t= 3,373, df=48, p<.05). Conclusion: Music therapy has significant effect in reducing preoperative anxiety levels of patients. Keywords: Anxiety, preoperative, music therapy